Truth-telling and the regulator: Evidence from a field experiment with commercial fishermen - Moritz A. Drupp; Menusch Khadjavi; Martin F. Quaas (Kiel Institute for the World Economy (IfW), 2016)
Understanding what determines the extent to which economic agents tell the truth to their regulating authority is of major economic importance, from banking to environmental protection. To this end, we examine truth-telling of German commercial fishermen in an artefactual field experiment. Their regulator, the European Union (EU), has recently enacted a ban on discarding unwanted fish catches to the sea, without yet increasing monitoring activities. The regulator thus depends on fishermen's truth-telling, while standard economic theory predicts substantial self-serving dishonesty. Using a coin- tossing task, we test whether truth-telling in a baseline setting differs from behavior in two treatments that exploit fishermen's widespread ill-regard of the EU. We find that fishermen misreport coin tosses to their advantage, albeit to a lesser extent than standard theory predicts. Misreporting is stronger among fishermen in a treatment where they are faced with the EU flag, suggesting that lying towards their ill-regarded regulator is more substantial. Yet, some fishermen are more honest in a control treatment where the source of EU research funding is revealed additionally. Our findings imply that regulators can influence truth-telling behavior by means of their regulatory approaches and communication strategies.
Keywords: C93; D63; Q22; K32; K42; L51; 330; truth-telling; lying; field experiment; regulation; fishermen